2020
DOI: 10.2991/chi.d.200220.001
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Endoscopy Affects Patient Management in Gastrointestinal Graft-Versus-Host Disease

Abstract: Graft versus host disease (GVHD) of the gut is associated with significant morbidity and mortality after allogeneic hematopoietic cell transplant (allo-HCT). No guidelines exist regarding repeat endoscopy after failure of first-line treatment with steroids. We aimed to study if repeat endoscopic biopsy can be helpful in these patients to guide treatment decisions. We retrospectively reviewed medical records of all patients who underwent repeat endoscopy for clinical suspicion of gastrointestinal (GI) GVHD afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Moreover, adverse events related to endoscopy cannot be overlooked, such as ventilatory problems, linked to sedation and anaesthesia, as well as perforation and bleeding, secondary to the endoscopic procedure [ 40 , 41 , 42 ]. Conversely, endoscopy should be encouraged to differentiate CMV-associated PLE and graft-versus-host disease in transplant patients [ 43 , 44 ]. Even though the histological findings are ambiguous, as they may be similar to a CMV infection (epithelial apoptosis, crypt abscesses, degeneration of crypt cells, nuclear atypia) [ 45 ], our study showed that the CMV PCR on digestive tissue was relevant for the diagnosis in immunosuppressed patients and will help differentiate both diagnoses in this specific indication.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adverse events related to endoscopy cannot be overlooked, such as ventilatory problems, linked to sedation and anaesthesia, as well as perforation and bleeding, secondary to the endoscopic procedure [ 40 , 41 , 42 ]. Conversely, endoscopy should be encouraged to differentiate CMV-associated PLE and graft-versus-host disease in transplant patients [ 43 , 44 ]. Even though the histological findings are ambiguous, as they may be similar to a CMV infection (epithelial apoptosis, crypt abscesses, degeneration of crypt cells, nuclear atypia) [ 45 ], our study showed that the CMV PCR on digestive tissue was relevant for the diagnosis in immunosuppressed patients and will help differentiate both diagnoses in this specific indication.…”
Section: Discussionmentioning
confidence: 99%
“…Non-specific signs of lower GI acute GVHD on CT scan include bowel wall thickening, abnormal mucosal enhancement, bowel dilatation and air or fluid levels suggestive of ileus 91 . Endoscopic manifestations of acute GVHD include spotted or diffuse erythema, patchy erosion, scattered ulceration and active bleeding [92][93][94] (Fig. 4d).…”
Section: ();mentioning
confidence: 99%
“…In this new issue of Clinical Hematology International , you will read some high-level clinical reviews [ 2 , 3 ] and original reports [ 4 5 ], in addition to a diverse set of material. We hope you will continue to enjoy the IACH activities.…”
mentioning
confidence: 99%